Bta-miR-223 Targeting CBLB Contributes to Resistance to Staphylococcus aureus Mastitis Through the PI3K/AKT/NF-κB Pathway - Han, Shuo; Li, Xinli; Liu, Juan; Zou, Ziwen; Luo, Lin; Wu, Rui; Zhao, Zhihui; Wang, Changyuan; Shen, Binglei (Frontiers in Veterinary Science, 2020)
Bovine mastitis is an inflammatory condition of the mammary gland often caused by (Staphylococcus aureus) S. aureus infection. The aim of this study was to identify mastitis-related miRNAs and their downstream target genes, and therefore elucidate the regulatory mechanisms involved in disease progression and resistance. Three healthy and three mastitic cows were identified on the basis of the somatic cell count and bacterial culture of their milk, and the histological examination of udder tissues. High-throughput RNA sequencing and bioinformatic analyses revealed that 48 differentially expressed miRNAs (DEMs) in the mastitic udder tissues relative to the healthy tissues. Among 48 DEMs, the expression level of bta-miR-223 was the most up-regulated. Overexpression of the bta-miR-223 in Mac-T cells mitigated the inflammatory pathways induced by S. aureus-derived lipoteichoic acid (LTA). The Cbl proto-oncogene B (CBLB) was identified as the target gene of bta-miR-223, and the direct binding of the miRNA to the CBLB promoter was confirmed by dual luciferase reporter assay using wild-type and mutant 3'-UTR constructs. Furthermore, overexpression of CBLB in the LTA-stimulated Mac-T cells significantly upregulated PI3K, AKT, and phosphorylated NF-κB p65, whereas CBLB knockdown had the opposite effect. Consistent with the in vitro findings, the mammary glands of mice infected with 108CFU/100 μL S. aureus showed high levels of CBLB, PI3K, AKT, and p-NF-κB p65 48 h after infection. Taken together, bta-miR-223 is a predominant miRNA involved in mastitis, and bta-miR-223 likely mitigates the inflammatory progression by targeting CBLB and inhibiting the downstream PI3K/AKT/NF-κB pathway.